Behavior of reinforced concrete beams strengthened with CFRP rod panels CRP 195. (November 2018) - Jawdhari, Akram; Harik, Issam; Fam, Amir
Abstract: This paper investigates the behavior of reinforced concrete beams strengthened in flexure using externally bonded carbon fiber reinforced polymer (CFRP) rod panels (CRPs) fabricated using 4 mm rods spaced at 9.5 mm. The experimental program consisted of a control beam and three beams strengthened with either a continuous CRP, a spliced CRP with two half-length CRPs spliced through a 150 mm finger joint, or a spliced and end-anchored CRP. Spliced panel performed similar to the continuous one, with no debonding observed at finger joint. They resulted in a comparable strength increase relative to the non-strengthened control beam of 95 and 104%, respectively, and failed by concrete cover separation (CCS) at CRP end. When the spliced CRP was end-anchored, the increase in strength was 195% relative to the control beam, with the finger-joint still intact, and the failure mode changed to intermediate crack-induced debonding (ICID). The analytical model, developed from sectional analysis and strength models for debonding failures, is capable of predicting the load-deflection response and ultimate loads, including the two observed debonding failures. For CCS failure, two models are presented, one is based on the concrete tooth model, and the other on the shear capacity model. The ICID failure was based on limiting the CFRP strain in accordance with ACI 440.2R-17 design guide. Results showed a good correlation between analytical predictions and test data.